MODERN CONDITIONS OF DISTANCE LEARNING IN THE HIGHER EDUCATION SYSTEM - Hakimova Mushtariybonu; Abduvalieva Sayyora Alisher qizi (Galaxy International Interdisciplinary Research Journal, 2024)
This article examines the current state of distance learning in higher education, analyzing the technological, pedagogical, and institutional conditions that shape its implementation. It highlights the challenges and opportunities presented by online education, drawing on recent research and case studies to provide a comprehensive overview of how higher education institutions are adapting to modern conditions.